Hubungan Indeks Massa Tubuh (IMT) dengan Kadar Glukosa Darah Puasa pada Dewasa di Wilayah Kerja Puskesmas Mantrijeron - Nita Aulia Pramesti; Havida Widyastuti; Lisa Wahyuningrum (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Fasting blood glucose (FBS) is an important indicator using acces the grades of glucose metabolism inside body. Body Mass Index (BMI) was currently used as an indicator of nutritional grades has correlation of risk metabolic disorders, including elevated fasting blood glucose grades. This reseach was purposelly to established the relationship among BMI also fasting blood glucose grades towards adults aged 30-60 years in the Mantrijeron Community Health Center (Puskesmas) working area. The reseach using observational analyzing design with a cross-sectional approach towards amount 49 respondents selectiong use tecnique purposive sampling. Data was including thru BMI measurements and fasting blood glucose examinations using a glucometer, then analyzing use the Spearman Rank Correlation test. The yields shown that respondent has a normal BMI category (44%), with a mean BMI of 25.5 kg/m² and a mean fasting blood glucose level of 94 mg/dL. The correlation exam test yields shown an r value of 0.167 with a p-value of 0.248 (p>0.05), its means there don’t has significant relationship among BMI also fasting blood glucose grades. This study concluded that BMI was not significantly associated with fasting blood glucose grades in adults range aged 30-60 years. Regular blood glucose testing and a healthy lifestyle are still necessary to prevent metabolic disorders and diabetes.